Культурна належність окремих поховань «нижньомихайлівського» типу - Отрощенко, В.В.; Рассамакін, Ю.Я. (Археологія, 1990)
В статье аргументируется принадлежность к черногоровскому типу памятников киммерийской культуры погребения 2(8) в кургане 1/3 у с. Грушевка Днепропетровской обл. и погребения 3 кургана 2 у с. Соколовка Николаевской обл., которые ошибочно были отнесены к энеолитической эпохе. Авторы подчеркивают различие в керамике энеолита и раннего железного века, имеющей некоторое внешнее сходство. Природа выявленных ошибок в атрибуции погребений — очевидные просчеты при раскопках и публикации материалов.
Для избежания подобных ошибок в будущем требуется профессиональный подход к археологическому первоисточнику. Burial 2 (8) in the burial mound 1/3 near the vil. Grushevka of the Dnepropetrovsk region and burial 3 from the burial mound 2 near the vil. Sokolovka of the Nikolaev region which were by mistake attributed to the eneolithic epoch are proved to refer to the Chernogorian type of monuments of the Cimmerial culture. The authors emphasize a difference in the pottery of the early eneolithic and the early Iron Age which are a bit evident errors made under excavations and publication of the materials. A professional alik visually. Nature of the revealed mistakes in the attribution of burials lies in the approach to the archaeological source is necessary to eliminate such mistakes in future.